2014
DOI: 10.1007/s00380-014-0550-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in ward-to-cath lab systolic blood pressure predicts long-term adverse outcomes after drug-eluting stent implantation

Abstract: We sought to investigate the effect of ward-to-cath lab blood pressure (BP) differences on long-term clinical outcomes in patients undergoing percutaneous coronary intervention (PCI) with drug-eluting stent (DES). There are limited data available on the association between PCI with DES and BP differences on long-term clinical outcomes. This study enrolled 994 patients who underwent PCI with DES from March 2003 to August 2007. Resting BP was measured in a ward environment before transfer to the cardiac catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In one previous study of patients with chronic kidney disease who developed CIN, the incidence of postprocedural hypotension was as high as 17.5%, whereas the preprocedural rate was only 5.3% [11]. A postprocedural decrease in SBP is likely to reflect cardiac dysfunction, vasovagal reflex, hypovolaemia, arterial stiffness or inappropriate antihypertensive treatment [12][13][14].…”
Section: Discussionmentioning
confidence: 95%
“…In one previous study of patients with chronic kidney disease who developed CIN, the incidence of postprocedural hypotension was as high as 17.5%, whereas the preprocedural rate was only 5.3% [11]. A postprocedural decrease in SBP is likely to reflect cardiac dysfunction, vasovagal reflex, hypovolaemia, arterial stiffness or inappropriate antihypertensive treatment [12][13][14].…”
Section: Discussionmentioning
confidence: 95%
“…NLR was defined as the ratio of the neutrophil count to the lymphocyte count. The method of BP measurement has been described previously [ 10 ]. In brief, patients were measured with the resting right arm BP in the supine position in a ward setting, before transfer to the catheterization laboratory, where it was measured again after the patients had laid down on the catheterization laboratory table prior to any arterial puncture or PCI (ward-to-catheterization laboratory BP difference).…”
Section: Methodsmentioning
confidence: 99%
“…It would be very informative if we could predict long-term prognosis of the patients who are going to have CAG or PCI before these operations begin. Her et al [ 10 ] suggested that changes in peri-procedural BP may be significantly associated with major adverse cardiac events and reported that a difference in the ward-to-catheterization laboratory systolic BP (SBP) (ΔSBP) of > 20 mmHg was related to an increased rate of all-cause death and cardiac death (CD) after drug-eluting stent (DES) implantation. In actual clinical practice, minimally invasive or non-invasive, inexpensive diagnostic tools are preferred over invasive diagnostic tools in view of cost and patient safety [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative method is visit-tovisit BP monitoring, which allows multiple measurements and provides information about variability that is not obtained from a traditional clinic measurement. Increased BP variability, including visit-to-visit variability, was proven to be associated with subsequent stroke, [13][14][15][16] coronary artery disease [13,14,[16][17][18], and allcause mortality [19,20] in the general population. However, the association between visit-to-visit BP variability and progression of AS has not been elucidated in CHD patients.…”
Section: Introductionmentioning
confidence: 99%